Avaliação da transição agroecológica em agroecossistemas de agricultura familiar - Silva, Maria Janaína Nascimento (2020)
Today, there are a multitude of problems caused by the indiscriminate use of natural resources, and most of them are due to conventional agriculture. The central objective of this style of agriculture is the maximization of capital, in order to obtain profit and this generates a disconnect between the social, environmental and economic spheres. In contrast to this model, Agroecology emerges with the sustainable production aspect of the agroecosystem, causing the rupture of pre-existing paradigms in agriculture, starting from the Agroecological Transition. In this sense, the study of local communities that are part of this process, contributes to the sustainability assessment of agroecosystems, enabling the analysis of which paths we need to strengthen and follow to explore natural resources without major damage. For this, the development of research that dialogs with the local need for family farming in rural settlements and communities, which are in the process of Agroecological Transition, allows us a theoretical and practical contribution to further advances in sustainable agricultural practices. This paper analyzes levels of agroecological transition in five agroecosystems based on family agroecological agriculture. Based on environmental, social and economic indicators, which indicate the transition from conventional agriculture to agroecological agriculture. For this, this work was conducted in agroecosystems located in the Paulo Freire agrovillage, Maísa settlement, Rio Grande do Norte. Where, indicators such as seed bank, trade fair, family participation, food sovereignty, among others, were evaluated. These indicators were quantified on a numerical scale of 1, 2 and 3 representing the initial level of agroecological transition, intermediate level of agroecological transition and desirable level of agroecological transition, respectively. Evaluated using participatory methodologies such as semi-structured interviews. At the end of the analysis, it was concluded that the agroecosystems in question are at an intermediate level of agroecological transition, where some factors influenced the better performance of others, needing more attention regarding the agroecological principles